Competitiveness of the Hungarian elite sport system. (Final report submitted to the IOC Olympic Studies Centre in the framework of the PhD Students Research Grant Programme 2015) - Gulyás, E. (IOC Olympic Studies Centre, 2016)
Summary: This paper presents the initial results of significant research conducted under the IOC PhD Student Research Grant Programme with the support of the Hungarian Olympic Committee. The main objectives of the research were to understand why Hungary is successful in specific sports and to explore the relationship between elite sport policy systems and success in international competitions. The increasing international sporting competition forces governments to invest more money in elite sport development just so they can maintain their elite sport success as the supply of medals remains basically constant. A macro- and meso-level analysis were conducted within the framework of this research. The data collection based on information gained through an overall questionnaire and interviews with main stakeholders, coaches and athletes within national sport federations (De Bosscher, 2010). The data collection was focused on the sixteen prioritised sport federations and the five team sports which benefited from a tax relief system. Secondary data were collected regarding the national public funding for sport, elite sport and sport by sport since 2006, and an Infostrada database was used to analyse historical performance in the different disciplines and compare Hungarian performance with those of other countries. This research will provide information to policy makers about the competitive position of Hungary in elite sport and, in this respect, explore the critical success factors which will allow Hungary to assess how best to manage its future success in an increasingly competitive international environment.